Comparative Perspectives on the Keeping of Animals in Sectional (Strata) Title Schemes - Van der Merwe, Cornelius G (Potchefstroom Electronic Law Journal, 2022)
The aim of this article is to provide comparative perspectives on the keeping of animals in sectional title schemes by analysing the conduct rule for the keeping of animals, reptiles, and birds in the provisions of the Sectional Titles Schemes Management Act. This investigation is prompted by the approval of new pet rules by the chief ombud and the provisions of the Community Schemes Ombud Service Act on adjudication orders available for nuisance caused by animals. The Act further allows the body corporate to record a new scheme governance rule or to declare a scheme rule invalid. The topics to be discussed are: the types of animal kept in sectional title schemes; the written approval of the trustees for the keeping of animals which may not be withheld unreasonably; whether the body corporate may adopt a scheme rule containing a blanket prohibition on the keeping of animals in a sectional title scheme; the reasonable conditions which may be attached to trustee approval; the withdrawal of approval if the conditions are breached; the requirements for a rule restricting the keeping of a kind of animals or animals with specific characteristics in a scheme; and the deemed approval for the keeping of guide, hearing, and assistance animals in a sectional title scheme.